HUBUNGAN PENGETAHUAN GIZI, POLA MAKAN DENGAN STATUS GIZI PADA IBU DI DESA PAHALETEN KECAMATAN KAKAS KABUPATEN MINAHASA - Riani E. Tiha; Nonce N. Legi; Rivolta G.M. Walalangi (POLTEKKES KEMENKES MANADO, 2016)
Balanced nutrition problems in Indonesia is still a substantial problem. The problem of thepoor economy and limited knowledge of nutrition. Nutritional knowledge would affect eatinghabits or eating behavior of a society. The success of development could have a negativeimpact, among others, the occurrence of overweight as a result of lifestyle changes includediet. The modern diet that is higher than the physical akftifitas will cause nutritional problemslebih.Tujuan this study to determine the relationship between maternal nutrition knowledge,dietary and nutritional status in the village PahaletenMinahasa District of KakasThe design of this penetitian Cross Sectional Study. The study only make observations andmeasurements of variables at one particular time. Measurement variables are not limited tobe just about the same time. Total population of 248 people and the number of respondentsas many as 38 people. Data collected include general data, knowledge of nutrition, diet andnutrition stattus. Data obtained from interviews, questionnaires knowledge, measurement ofnutritional status, and the questionnaire FFQ.Of the 38 respondents there were 20 people (52.6%) having the nutritional status of obesitywith the knowledge level of <60%. While diet with nutrient status have a meaningfulrelationship in which the value of p <0.05 were obtained through statistical tests TestFisher.Berdasarkan There was no relationship between the Nutritional Sciences Nutritionalstatus However the correlation between diet and nutritional status of the mother